Tale after Tale after Tale: The Lost Chance of a Great Project - Wielenga, Friso (BMGN - Low Countries Historical Review, 2013)
Chris van der Heijdens voluminous dissertation on the culture of memory in the Netherlands of the Second World War (Dat nooit meer [Never Again]) is disappointing on several counts: methodologically it does not meet the scientific standards, that should be expected from an academic historian and the book is more a compilation of stories than a coherent analysis. Moreover the author has a biased view on many aspects of his research theme. To mention only two examples, his view on the purge of Nazi collaborators is extremely simple and one-sided and this also applies to his description of the way the resistance against the Nazis was viewed after the war. Furthermore a fundamental problem is his moralistic tone in judging the way people looked back at the occupation period. Those who fit into his own view of the ‘grey past’ are treated approvingly, others are dispensed with in an unfair or ironical way. Van der Heijden does not see that black, white or grey, are not the right terms to describe the attitude of people during the war: the view has to be multicoloured. This also applies to the description of the culture of memory after 1945 and it’s just that colourfulness that is dramatically lacking in this book. This review is part of the discussion forum 'Dat nooit meer' (Chris van der Heijden).